Kualitas Sale Pisang Goreng Pada Berbagai Tingkat Kematangan Buah Pisang Raja Siem (Musa Acuminata) dan Potensinya Dalam Pendidikan Lingkungan Hidup - Diyahwati, Diyahwati; Wiharto, Muhammad (Agricultural Technology Education Study Program, 2024)
Raja Siem Banana (Musa acuminata) is a type of banana that can be used as a fried banana sale. This study aims to determine the quality of fried banana sale ripeness levels. The method used was a Completely Randomized Design (CRD), the level of ripeness of banana fruit with four levels after picking: 0 day, 1 day, 2 days and 3 days. The parameters observed were water content, total sugar content, oil content, and organoleptic. Analysis of the potential of fried banana sale for environmental management was carried out by reviewing the literature on relevant sources from journals. The study’s proximate water content test results met the standard of 8.79% - 17% (maximum 40%). The lowest total sugar content was 45.11%, and the highest was 70.22%. The lowest oil content was 10%, and the highest was 12.53%, meeting the maximum standard of 30%. The fried banana sales were produced based on the overall preference test. The panellists gave an average score of 4.2 in liking colour, taste, texture, and aroma. Processing Raja Siem bananas into a fried banana sale is one step in seeking optimal environmental conditions due to banana rot to create good environmental conditions.